Can the Case Report Withstand Ethical Scrutiny?. Issue 6 (8th December 2019) - Rosoff, Philip M.
Abstract: Since antiquity, doctors have employed case reports as an essential and ongoing part in communicating information about patients and their diseases to their colleagues and, at times, to the wider, nonmedical world. Given how useful case reports have been, a legitimate and persuasive argument could be made to retain them in modern medical literature. But there is an emerging problem with case reports. As the ability to publish and disseminate the information contained in them has become easier, the capacity for individuals to maintain their privacy and restrict access to their personal information has become more strained, and it has become more difficult for doctors who tell clinical stories to respect the confidentiality of their patients while still communicating the pertinent details of their cases. Does the acknowledged educational and scientific value of (some) case reports justify the threat to personal privacy that may be entailed by the format itself?